Die Kaiserliche Archäologische Kommission und die Erforschung der klassischen Altertümer im nördlichen Schwarzmeergebiet (1859–1917) - Vinogradov, Jurij A. (Hyperboreus, 2014)
The article deals with the history of the Imperial Archaeological Commission since its foundation in 1859 and its leading role in the revelation and study of the ancient sites of Pantikapaion, Phanagoreia, the Bosporus mounds, Chersonesos Taurike, Olbia, and Berezan. The author places emphasis on the activity of A. A. Vasil’čikov, N. P. Kondakov, I. E. Zabelin, V. V. Latyšev, B. V. Farmakovskij among others.